Research methodology : from philosophy of science to research design - Novikov, A. M. [ (Aleksandr Mikhailovich)] , 1941-; Novikov, D. A. [ (Dmitrii Aleksandrovich)] , 1970- (Communications in cybernetics, systems science and engineering, 2013)
"This book distinguishes itself in its integrated approach towards scientific research, and studies the basics of the methodology of scientific research and the organization of scientific activity from the viewpoint of systems science and system analysis. The book discusses the basics of the methodology including philosophical, psychological, epistemological and ethical/aesthetical foundations, the characteristics of scientific activity, including principles of scientific cognition, the means and methods of scientific research, the organization of a research implementation process and its chronological structure and finally, the organization of a collective scientific research design"-- Provided by publisher